Makna Gadis-gadis yang Bijaksana dan yang Bodoh dalam Matius 25:1-12 - Ariyanto; Simatauw, Marfy (Sekolah Tinggi Teologi Borneo, 2020)
Abstract: In the Gospels it also records the day of Jesus' second coming in a parable. Regarding Hissecond coming, as told in the Book of Matthew about